The Implementation of Principal Supervision in Building Teacher Performance in Elementary Schools - Lisda, Hafia; Ghani, Abd. Rahman A; Fatayan, Arum (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study intends to assess how the principal implements academic supervision to enhance teacher performance in elementary schools. The primary objective of this study is to provide recommendations to schools regarding the implementation of supervision, whether there are aspects that need to be stopped, improved, or continued without changes. Secondary objectives include evaluation of the design, installation, process, and product of the supervision implementation. This study uses an evaluative approach with the Discrepancy Evaluation Model (DEM), which emphasizes identifying gaps between standards (Standard/S) and actual performance (Performance/P) in each implementation stage. Data was collected through interviews, observations, and documentation studies. In this study, the research subjects were the principal, vice principal, 18 teachers, 30 students, and 6 school committee members. The evaluation results show that at the design stage of supervision there are still gaps between standards and performance, especially in the systematic and realistic aspects, so that it is in the